2007
DOI: 10.1111/j.1365-3040.2007.01735.x
|View full text |Cite
|
Sign up to set email alerts
|

Chlororespiration is involved in the adaptation of Brassica plants to heat and high light intensity

Abstract: Two species of Brassica were used to study their acclimation to heat and high illumination during the first stages of development. One, Brassica fruticulosa, is a wild species from south-east Spain and is adapted to both heat and high light intensity in its natural habitat, while the other, Brassica oleracea, is an agricultural species that is widely cultivated throughout the world. Growing Brassica plants under high irradiance and moderate heat was seen to affect the growth parameters and the functioning of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
52
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(54 citation statements)
references
References 39 publications
1
52
0
1
Order By: Relevance
“…This was the case in Ranunculus glacialis, an alpine plant, when it was acclimated to high light and low temperature (17); in the halophyte Thellungiella halophila when it was exposed to salt stress (18); and in Brassica fruticulosa when it was exposed to elevated temperature and high light (19). Although these findings support the hypothesis that PTOX may serve as a safety valve under stress conditions, they are in direct conflict with the data of Rosso et al (20).…”
mentioning
confidence: 71%
“…This was the case in Ranunculus glacialis, an alpine plant, when it was acclimated to high light and low temperature (17); in the halophyte Thellungiella halophila when it was exposed to salt stress (18); and in Brassica fruticulosa when it was exposed to elevated temperature and high light (19). Although these findings support the hypothesis that PTOX may serve as a safety valve under stress conditions, they are in direct conflict with the data of Rosso et al (20).…”
mentioning
confidence: 71%
“…Plants have developed individual tolerance mechanisms to cope with the environmental stress during evolutional processes, as the mechanisms are much varied between species and different groups (Quiles, 2006;Diaz et al, 2007). Under environmental stress conditions, such as salinity and high irradiance, plants show the ingenious adaptations at all levels of organization, from morphological to biochemical, molecular, and physiological levels (Diaz et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Stress usually refers to an unfavorable condition in which an external factor exerts undesirable influence on plants, and it can cause the happening of special responses in all physiological levels of an organism (Quiles, 2006;Diaz et al, 2007;Ibanez et al, 2010). Plants have developed individual tolerance mechanisms to cope with the environmental stress during evolutional processes, as the mechanisms are much varied between species and different groups (Quiles, 2006;Diaz et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neither did the concentration of photosynthetic pigments or the F v /F m values show any significant decrease after the stress photoperiods, suggesting that chloroplasts are protected by mechanisms that dissipate excess excitation energy to prevent damage to the photosynthetic apparatus under adverse conditions. In this respect, we have reported that chlororespiration and cyclic electron flow pathways are involved in the tolerance to adverse factors in both sun and shade species (Díaz et al, 2007;Gamboa et al, 2009;Ibañez et al, 2010;Quiles, 2006;Tallón & Quiles, 2007). However, when the light response curves for the relative electron transport rate were depicted, differences were observed between control plants and those exposed to stress photoperiods, the capacity of photosynthetic electron transport being lower in plants exposed to stress photoperiods in both species.…”
Section: Discussionmentioning
confidence: 93%